2017
DOI: 10.9778/cmajo.20170002
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus testing and linkage to care in a Canadian urban tertiary referral centre: a retrospective cohort study

Abstract: Many HBsAg-positive people in Calgary did not receive the recommended laboratory assessments. The results highlight the necessity of continual public health efforts to screen for chronic HBV infection in Canada and to ensure adequate follow-up in order to reach the World Health Organization's goal of viral hepatitis elimination by 2030.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…However, HBV remains endemic in many areas of the Southeast Asia region and Africa, which have an estimated prevalence of 6.2% and 6.1%, respectively [ 1 , 3 ]. Within Canada, there are an estimated 260,000 chronically infected individuals (0.76% estimated prevalence), with the majority of those with CHB are new Canadians from endemic areas [ 3 , 4 ]. Within the Calgary Health Zone in Alberta, Canada, our prior research study reported a total of 1214 individuals (0.10% of population within Calgary zone) who tested positive for HBsAg within a single calendar year (2014) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, HBV remains endemic in many areas of the Southeast Asia region and Africa, which have an estimated prevalence of 6.2% and 6.1%, respectively [ 1 , 3 ]. Within Canada, there are an estimated 260,000 chronically infected individuals (0.76% estimated prevalence), with the majority of those with CHB are new Canadians from endemic areas [ 3 , 4 ]. Within the Calgary Health Zone in Alberta, Canada, our prior research study reported a total of 1214 individuals (0.10% of population within Calgary zone) who tested positive for HBsAg within a single calendar year (2014) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Within Canada, there are an estimated 260,000 chronically infected individuals (0.76% estimated prevalence), with the majority of those with CHB are new Canadians from endemic areas [ 3 , 4 ]. Within the Calgary Health Zone in Alberta, Canada, our prior research study reported a total of 1214 individuals (0.10% of population within Calgary zone) who tested positive for HBsAg within a single calendar year (2014) [ 4 ]. The majority of these cases are likely newly diagnosed CHB carriers, many of which lacked appropriate monitoring and management of their disease.…”
Section: Introductionmentioning
confidence: 99%
“…Our finding of suboptimal laboratory assessment was in line with previous studies that found ALT testing in 97–98%, HBV DNA testing in 44–56% and HBeAg testing in less than 52% of HBsAg-positive patients within six months after diagnosis. 31 , 32 In our study, 77% had ALT testing, 42% had testing for HBV DNA and 80% had HBeAg testing. The accurate use of laboratory diagnostics can help differentiate those with need of antiviral therapy from those who need to be monitored for disease progression.…”
Section: Discussionmentioning
confidence: 52%
“…In Alberta, administrative data on demographic characteristics and laboratory data were collected for 3 participating sites from the Alberta Health Services data repository, as previously described. 10 Crosssectional data analysis was done on the most recent patient record submitted. Fifteen sites submitted clinical data from 8 provincial health jurisdictions.…”
Section: Methodsmentioning
confidence: 99%